2008
DOI: 10.1002/em.20363
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gene methylation by genistein or lycopene in breast cancer cells

Abstract: Dietary agents with chemopreventive potential, including soy-derived genistein and tomato-derived lycopene, have been shown to alter gene expression in ways that can either promote or potentially inhibit the carcinogenic processes. To begin to explore the mechanisms by which these agents may be acting we have examined the DNA methylation modulating capacity of genistein or lycopene for several genes relevant to breast cancer in the breast cancer cell lines MCF-7 and MDA-MB-468, as well as in immortalized but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(122 citation statements)
references
References 69 publications
5
115
1
1
Order By: Relevance
“…Reactivation of RARβ by the reversal of DNA hypermethylation by genistein was also observed in human prostate cancer LNCaP and PC3 cells (65). Treatment of human breast cancer MDA-MB-468 cells with low concentrations of genistein restored the expression of GSTP1 gene by partially demethylating its promoter (66). In human prostate cancer PC-3, DU-145, and LNCaP cell lines, in which promoters of GSTP1 and EPHB2 are strongly methylated, treatment with soy isoflavones genistein and daidzein caused demethylation of these promoters and increased protein expression (67).…”
Section: Genistein and Soy Isoflavonesmentioning
confidence: 77%
See 1 more Smart Citation
“…Reactivation of RARβ by the reversal of DNA hypermethylation by genistein was also observed in human prostate cancer LNCaP and PC3 cells (65). Treatment of human breast cancer MDA-MB-468 cells with low concentrations of genistein restored the expression of GSTP1 gene by partially demethylating its promoter (66). In human prostate cancer PC-3, DU-145, and LNCaP cell lines, in which promoters of GSTP1 and EPHB2 are strongly methylated, treatment with soy isoflavones genistein and daidzein caused demethylation of these promoters and increased protein expression (67).…”
Section: Genistein and Soy Isoflavonesmentioning
confidence: 77%
“…Demethylation of RARβ2 and HIN-1 genes in immortalized non-tumorigenic MCF10A fibrocystic breast cells however was observed after 2 weeks of lycopene treatment. The study shows that lycopene has direct DNA demethylating activity (66).…”
Section: Lycopenementioning
confidence: 92%
“…The ability of genistein to change the methylation status was observed in several other studies. Genistein was shown to partially demethylate the promoter of the GSTP1 tumor suppressor gene in MDA-MB-468 breast cancer line (King-Batoon et al, 2008). Another study shown the change of methylation status in mice prenatally exposed to genistein (Vanhees et al, 2011).…”
Section: Signalling Pathways Influenced By Genistein In Microarrays Pmentioning
confidence: 97%
“…While 1-carbon metabolism and folate availability have, to date, been a major focus of attention, it is increasingly apparent that altered DNA methylation is not simply an issue of the bioavailability of methyl groups. For example, the isoflavone, genistein, has profound effects on DNA methylation but has no involvement in 1-carbon metabolism (King-Batoon et al, 2008).…”
Section: Diet and Epigeneticsmentioning
confidence: 99%